Taller de teatro Express para desarrollar la expresión oral en los estudiantes de una Institución Educativa-Trujillo, 2018 - Flores García, Naysha Selene (2019)
The main aim of this research was to determine the extent to which the Express theater Workshop develops the oral expression in the students of an Educational Institution-Trujillo, 2018. For this purpose, it was applied a test to measure oral expression which was composed of 12 items in a sample of 64 students. The type of this research was applied, since it sought to provide a solution to the problem identified through the application of an Express theater workshop. Finally, the results achieved in this reserach have shown a significant influence between the Express theater workshop and the oral expression